The role of integrins in eye diseases - Żaworonek, Justyna; Żelazowska-Rutkowska, Beata; Bryl, Anna; Mrugacz, Małgorzata; Cylwik, Bogdan (Klinika Oczna / Acta Ophthalmologica Polonica, 2018)
Integrins belong to the cell adhesion molecules. Integrins and their ligands play the main role in physiological and pathological processes: cell migration, cell differentiation, hemostasis, adhesion, angiogenesis and wound healing. The main task of integrin is to facilitate biochemical and mechanical signal transmission across the plasma membrane in a bidirectional manner. The signals trigger integrin transformation from an inactive form into a ligand-binding state. Integrins play an important role in physiological (embryogenesis, tissue growth and development) and pathological (allergy, inflammation, cancer) processes, being particularly involved in dry eye disease, age-related macular degeneration and diabetic macular edema. Improved understanding of integrins can contribute to the development of new diagnostic methods and advances in immunotherapy.